Language Dynamics and Academic Performance in Rural Xitsonga Speaking Grade 10 History Classrooms - Sombani, Khensani Eunice; Maluleke, Nkhensani (Journal of Languages and Language Teaching, 2025)
This study explores the influence of the Language of Learning and Teaching (LoLT) on the academic success of Xitsonga-speaking Grade 10 students in rural History classrooms in four Mopani district's quintile 1 schools in Limpopo Province. Quintile 1 schools are those considered by the government of South Africa as being in poor communities that cannot afford to pay for their children's education.Â  Utilising a mixed methods approach, the investigation involved four classroom observations, 4 teacher interviews, and four focus group discussions with learners alongside the Solomon Four quasi-experiment for quantitative data collection using the four classrooms. The classes were used as intact groups of n=20, with a total of 80 learners. The results indicate a negative correlation between the learners' academic performance and their proficiency in LoLT. Furthermore, this study reveals that a disconnect between the learners' first language used at home and the English language of instruction contributes to educational challenges. It was observed that when teachers employed the learners' first language, the educational outcomes improved significantly, underscoring the effectiveness of using learners' native language in the learning process. The study suggests that integrating translanguaging into the multilingual educational system can align with linguistic realities and foster superior academic results. The findings advocate for education stakeholders to recognise and utilise translanguaging to make the curriculum more accessible and engaging, thus improving academic achievements in Xitsonga-dominant classrooms.Â